Jamu: Javanese Doping During the Covid-19 Pandemic - Akhodza Khiyaaroh; Atik Triratnawati (Indonesian Journal of Medical Anthropology, 2021)
Jamu is a part of traditional medicine that draws many people's attention today. This can be seen in the increasing consumption of jamu in Indonesian society. This increase can be influenced by the decision of the Indonesian people to consume jamu as an effort to prevent Covid-19. This study revealed the reasons behind the choice of jamu as an effort to prevent Covid-19 in some Indonesian people, especially in rural Javanese people where jamu is very closely related to their lives. This research was conducted in Mojorejo Village, Kebonsari District, Madiun Regency by involving 20 informants obtained through purposive sampling technique. This research was conducted from April to June 2021. The ethnographic method was used to enable the researchers to dig deeper into the informants' experiences regarding herbal medicine. The researchers analyzed the research data by coding and included secondary data to enrich the findings. Rural Javanese people choose jamu as doping during the Covid-19 pandemic for three reasons, including the tradition of drinking jamu, its immune booster properties, and the 3M (mudah, murah, manjur) [Easy, Cheap, Effective] aspects of jamu. Jamu ingredients that include ginger, curcuma, aromatic ginger, turmeric, and tamarind are believed to be able to boost their immune system during the pandemic.